(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
In the context of the transformation of agricultural education and the implementation of the competency-based approach, there is an increasing need to rethink the professional competencies of teachers at agricultural universities. This article analyzes the structure of agropedagogical competencies, their specific features, and the ways in which they are formed in the context of modern educational requirements.